Electroacupuncture alleviates anxiety and modulates amygdala CRH/CRHR1 signaling in single prolonged stress mice. Issue 4 (August 2022) - Zhu, Jing; Wang, Chang; wang, Yu; Guo, Chunxia; Lu, Pingping; Mou, Fangfang; Shao, Shuijin
Background: Post-traumatic stress disorder (PTSD) is an anxiety-related psychiatric disorder, manifesting high comorbidity with anxiety disorders. Its underlying neurobiological mechanisms have been associated with hypothalamic–pituitary–adrenal (HPA) axis dysfunction and stress hormones. Corticotropin-releasing hormone (CRH) is a primary stress hormone, expressed in the hypothalamus and amygdala. Electroacupuncture (EA) can improve mood disorders, but its mechanisms have not been fully elucidated. The aim of this study was to observe the effect of EA on PTSD and explore the related mechanisms. Methods: We used single prolonged stress (SPS) mice to establish a PTSD model, and EA was performed after SPS or 7 days later for a week. Then we observed their fear and anxiety-like behavior through cue-induced fear condition tests, open field test and the elevated zero maze. CRH and CRH receptor 1 (CRHR1) protein levels in the amygdala were measured in SPS mice after EA intervention. Results: We found that EA at ST36 and GV20 improved fear and anxiety behavior in SPS mice. The amygdala CRH and CRHR1 protein levels increased in the SPS mice, and this effect was reversed by the EA intervention. CRHR1 inhibition by the CRHR1 antagonist NBI 27914 alleviated anxiety behavior in SPS mice. Conclusion: CRH/CRHR1 signaling in the amygdala may contribute to the anxiolytic effect of EA in SPS mice.